Um modelo multicritério para suporte à gestão de portfólio de serviços de TI em cenários de incerteza e risco - Pereira, João Paulo Ricarte (2024)
Appropriate decision-making in service portfolio management is essential for information technology (IT) service providers in the current globalized and highly competitive scenario. The evolution of cloud systems and increasing processing power ended up delegating to many systems the power to influence decision-making related to the most diverse subjects, motivated by the fact that model automation is more transparent, impartial and accurate in supporting decision-making . For modeling scenarios that involve multiple criteria in the decision, multi criteria decision-making methods have been widely used in the literature. In this research, a multi-criteria model based on the Analytic Network Process (ANP) method was proposed to support the IT service portfolio management process in scenarios involving uncertainty and risk. The model supported a problem related to information security of the portfolio's services. A triangulation was carried out between exploratory and bibliographical research, observation and case study based on data from a real company. As results obtained, we can mention the formation of a portfolio of IT services more suited to the business needs of service providers in today's highly competitive, risky and insecure environments.